MIRBOBO NAQSHBANDI ON THE MENTION OF THE SOUL AND ITS TYPES (Scientific journal of the Fergana State University, 2023)
In this article, the views, opinions and conclusions written by the mystic Mirbobo Naqshbandi about the soul, its dhikr and types of dhikr described in the work "Mir'otus solikin" ("The Mirror of the Seekers of the Right Path") were given and scientifically analyzed.